Il Cavallo de Leonardo: constelações da ideia (2ª Parte) / The Leonardo's Horses: constellations of the idea" (2nd part) - Conde, I. (CIES e-Working-Papers, nº 178, 2014)
Following previous approaches on the recognition of art and the imaginary museums, this text returns to Il Cavallo, the project of Leonardo da Vinci (1452-1519) to build a monumental statue when he was working for Ludovico Sforza (1452-1508), the Duke of Milan, for whom he painted the major fresco The Last Supper. Due to diverse circumstances the project for Il Cavallo was not executed. Only the drawings remained for the history and also for the myths around the visionary Leonardo. How did the idea emerge and how did it travel through time and the imaginary museum? In fact, the virtual horse that did not exist became to exist in versions built by admirers of Leonardo. Especially The Keepers of the Leonardo’s Dream, an American group that constructed the statue in the United States and gave it to Milan – where it was inaugurated in 1999. A sort of counter-gift from the imaginary museum, to paraphrase the dialectic of exchange or reciprocity in Marcel Mauss, Essai sur le Don/An Essay on the Gift (1896). Before the analysis of this case, the first part of the text begun with Leonardo and the project in the fifteenth century. This second part presents the Leonardo’s ideas and references for Il Cavallo, as well as the drawings for more horses along several years. It adresses the issues of authorship, artistic creativity and visual literacy.